Peer Connection Classifier Method for Load Balancing Technique - Safrianti, Ery (International Journal of Electrical, Energy and Power System Engineering, 2021)
A large number of requests for internet access causes a long response time resulting in an overload problem. This problem occurs in offices that provide public services such as the Soeman HS Regional Library and Archives Office in Riau Province. So that service work is not disrupted due to overload, network optimization is carried out using Load Balancing Techniques. Load Balancing will balance load traffic on two or more connection lines so that traffic can run optimally. The method used is the Peer Connection Classifier (PCC). This method will divide the load based on the source, destination address, and port address. All internet requests from users will go to the router that has been configured with Load Balancing with the PCC method. The router will manage outgoing requests from users through the Internet Service Provider 1 (ISP 1) line or ISP line 2 to be able to enter the internet connection. The test results show equal distribution of outgoing access to ISP 1 and ISP 2 lines so that there is no overload on any ISP lines. This configuration will be applied to the Mikrotik router using the Winbox application.